The effect of high speed strength training with heavy and low workloads on neuromuscular function and maximal concentric quadriceps strength - Mazani, A. A.; Hamedinia, M. R.; Haghighi, A. H.; Hedayatpour, N. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Dynamic strength training has been widely used to increase the ability of skeletal muscle to produce muscle force. Manipulating resistance training program variables has been commonly used as a tool to optimize maximum strength. This study examined the effects of 12 weeks of high-speed strength training with low and heavy workloads on muscle strength and neuromuscular function of quadriceps muscle.